2013
DOI: 10.4236/ojmm.2013.34034
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Class 1 and Class 2 Integrons in Clinical Isolates of Pseudomonas aeruginosa Collected from Seven Hospitals in Turkey: A Multicenter Study

Abstract: Pseudomonas aeruginosa is one of the leading nosocomial pathogens worldwide, and their infections are difficult to treat due to acquired resistance to many antibiotics. This study aimed to detect class 1 and 2 integrons and antibiotic susceptibility of clinical isolates of P. aeruginosa. Two hundred and five P. aeruginosa strains were collected from the seven general state hospitals in Turkey. They were characterized by antimicrobial susceptibility testing, screened for class 1 and class 2 integrons, and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…All P. aeruginosa isolates were 100% resistant to ampicillin, cefixime, cephalothin, nalidixic (32, 33). However, the frequency of class 1 integrons was very low (4.5%) in a multicenter study in Turkey (34). The frequency of intI1 in our study was similar…”
Section: Resultssupporting
confidence: 81%
“…All P. aeruginosa isolates were 100% resistant to ampicillin, cefixime, cephalothin, nalidixic (32, 33). However, the frequency of class 1 integrons was very low (4.5%) in a multicenter study in Turkey (34). The frequency of intI1 in our study was similar…”
Section: Resultssupporting
confidence: 81%
“…The most prevalent mechanism of aminoglycoside resistance are Aad and Aac families [13,14]. In the isolates of our study, the most common resistance is the aadA family (aadA5) and the dfrA family (dfrA17).…”
Section: Discussionmentioning
confidence: 80%
“…In these studies, the frequencies of class integrons were found 41.5% (44/106) in Brazil, 60% in England, 59% in France and 52% in Taiwan [11,13]. In Turkey, in a multicenter study of clinical P. aeruginosa isolates, the frequency of class 1 integrons was found to be 4.8% [14]. Resistance genes that cause aminoglycosides and β-lactams are frequently found on integrons in Pseudomonas and Enterobacteriaceae members.…”
Section: Discussionmentioning
confidence: 96%
“…The second class of integrons (Class 2) was found in transposon Tn7 and its derivatives, and its 3′ conserved segment containing five tns genes involved in the movements of the transposon, which have been reported most often in isolates within the Enterobacteriaceae family (13). As compared to Class 1 and 2, less is known about Class 3 integron which have been described as rare and found only in a 2 limited number of isolates including Serratia marcescens, Klebsiella pneumoniae, P. aeruginosa, P. putida, Alcaligenes xylosoxidans, and Delftia spp (14). Cassettes usually include a single ORF and downstream, an attC site which is an imperfect inverted repeat sequence related to a 60bp consensus sequence (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…As compared to Class 1 and 2, less is known about Class 3 integron which have been described as rare and found only in a 2 limited number of isolates including Serratia marcescens, Klebsiella pneumoniae, P. aeruginosa, P. putida, Alcaligenes xylosoxidans, and Delftia spp (14). Cassettes usually include a single ORF and downstream, an attC site which is an imperfect inverted repeat sequence related to a 60bp consensus sequence (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%